2001
DOI: 10.1002/1529-0131(200103)44:3<550::aid-anr103>3.3.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Levels of interleukin‐18 and its binding inhibitors in the blood circulation of patients with adult‐onset Still's disease

Abstract: Objective. Interleukin-18 (IL-18) is a proinflammatory cytokine that is involved in immunologically mediated tissue damage, but its bioactivity is regulated in vivo by its soluble decoy receptor, IL-18 binding protein (IL-18BP). This study was undertaken to determine levels of IL-18 and IL-18 binding inhibition in the blood of patients with adult-onset Still's disease (ASD).Methods Conclusion. These data indicate that systemic overproduction of IL-18 may be closely related to the pathogenesis of ASD, despite t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
49
0
4

Year Published

2002
2002
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(56 citation statements)
references
References 0 publications
3
49
0
4
Order By: Relevance
“…The notion of a central role for IL‐18 in the pathogenesis of AOSD is supported by our and other investigators' reports (12, 13). To examine the effects of IL‐18 on the in vitro apoptosis in AOSD patients, we investigated the frequency of apoptotic lymphocytes after 24‐hour incubation with rHuIL‐18.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The notion of a central role for IL‐18 in the pathogenesis of AOSD is supported by our and other investigators' reports (12, 13). To examine the effects of IL‐18 on the in vitro apoptosis in AOSD patients, we investigated the frequency of apoptotic lymphocytes after 24‐hour incubation with rHuIL‐18.…”
Section: Discussionsupporting
confidence: 82%
“…Zhang et al demonstrated that Th1 cells undergo activation‐induced cell death via the Fas/FasL pathway more readily than Th2 cells (11). Furthermore, we and other investigators have shown that patients with active AOSD often have high levels of serum interleukin‐18 (IL‐18) (12, 13). Dao et al indicated that IL‐18 might play a potential role in immunoregulation by enhancing FasL‐mediated cytotoxicity of murine Th1 cells (14).…”
Section: Introductionmentioning
confidence: 99%
“…The findings of previous reports, as well as those of our previous study, showed that serum interleukin‐18 (IL‐18) levels were markedly elevated and significantly correlated with disease activity in AOSD, indicating that IL‐18 is likely involved in the pathogenesis of this disease (16–18). ICAM‐1 expression can be induced in vitro and in vivo by IL‐18 (19–21), suggesting that it may be an important mechanism for regulating the inflammatory response.…”
Section: Introductionmentioning
confidence: 65%
“…Another study also showed the serum levels of sICAM‐1 were significantly higher in RA patients with systemic vasculitis than in patients with uncomplicated disease (36). The higher levels of serum sICAM‐1 in patients with active AOSD relative to patients with active RA may be an indicator of the higher systemic involvement and may account for the associated intense IL‐18 release observed in the former group (16, 18). However, bias may have been introduced in this study, because corticosteroid treatment used in patients with RA may suppress expression of ICAM‐1 in human monocytic cell lines (37).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Hoshino et al [27] reported elevated serum levels of TNF-α in AOSD patients. Recently, Kawashima et al [28] demonstrated that the proinflammatory cytokine IL-18 is markedly, and in this quantity rather specifically, elevated in the serum of AOSD patients during the acute phase of their disease. Because it has been shown that TNF-α induces the expression of IL-18 in synovial tissues [29], anti-TNF agents may lead to a reduction of IL-18 in AOSD patients.…”
Section: New Indications For Tnf-α-targeting Therapiesmentioning
confidence: 99%